Attitudes of the general public toward community pharmacy services in Saudi Arabia: A cross-sectional study - Almanasef, Mona (Frontiers in Public Health, 2023)
Aim This research was conducted to evaluate the attitudes of the general public toward community pharmacy services in Saudi Arabia. Methods The current study followed a cross-sectional design using an online anonymous self-administered questionnaire. The study was conducted in Saudi Arabia between February and April 2022. The study participants were selected and recruited using a convenience sampling strategy. The questionnaire was adapted from previous work and involved four sections: demographic information, use of community pharmacy, perception and willingness to use community pharmacist services, and barriers to approaching a community pharmacist for advice. Results and conclusions A total of 449 participants agreed to take part in this study and completed the questionnaire. Just above half (55%) of the participants indicated that they had visited a community pharmacy at least once a month over the last 12 months. The most frequently reported reason for visiting community pharmacies was to buy over-the-counter (OTC) medications. The majority (n = 318) of the participants were satisfied or highly satisfied with community pharmacy services in Saudi Arabia. A willingness to use community pharmacy services was expressed mostly for the essential community pharmacist roles, involving selecting over-the-counter products, management of minor ailments, selecting non-pharmaceuticals and receiving counseling on using medications. However, an unwillingness was noted to approach a community pharmacist for counseling on alcohol dependence and drug misuse. Lack of privacy in the community pharmacy was found to be the most frequently reported barrier that would hinder individuals from approaching community pharmacists to get help or advice. Policymakers in Saudi Arabia could considerably advance the community pharmacy practice and improve the public utilization of various community pharmacist services beyond their limited essential roles such as dispensing and counseling.